Reflectionless propagation of electromagnetic waves in inhomogeneous chiral plasma with small scale - Poverennui, M.V.; Erokhin, N.S. (Вопросы атомной науки и техники, 2013)
On the basis of an exactly solvable model of 1D-Helmholtz equation it is considered reflectionless propagation of transverse electromagnetic wave of circular polarization through a chiral inhomogeneous isotropic plasma with small-scale structures of high amplitude. Considered spatial profiles of plasma-dielectric chiral environment characterized by a number of free parameters that determine the characteristic scales of these structures, the spatial profile of the wave vector and wave field, the modulation of the dielectric permettivity etc. The model parameters are corresponding plasma without a magnetic field but with a small addition of chiral component (circular polarization of wave is provided by chirality). Numerical calculations of the spatial profiles for the wave number, the wave amplitude, the dielectric permettivity of chiral plasma have been performed. For some choice of the model parameters the wave number profile corresponds to the increase of the wave amplitude in the center of plasma layer. Variants are possible when the dielectric permettivity in its minimum is negative one and the chiral plasma contains sufficiently broad areas of opacity. Profiles of the dielectric permettivity and the wave vector can be qualitatively similar. Розглянуто на основі точно розв’язуваної моделі одновимірного рівняння Гельмгольця безвідбиткове поширення поперечної електромагнітної хвилі циркулярної поляризації через хиральну неоднорідну ізотропну плазму з мілкомасштабними структурами високої амплітуди. Розглянуті просторові профілі пламово-діелектричного оточення характеризуються великою кількістю вільних параметрів, що визначає характерні масштаби цих структур, просторового профілю хвильового вектора та поля хвилі, модуляції діелектричної проникності та таке інше. Модельні параметри відповідають плазмі без магнітного поля, але з малою додатковою хиральною компонентою (циркулярна поляризація хвилі забезпечена хиральністю). Виконано числові розрахунки просторових профілів хвильового вектора, амплітуди хвилі та діелектричної проникності хиральної плазми. Для деякого вибору модельних параметрів профіль хвильового числа відповідає збільшенню амплітуди хвилі в центрі плазмового шару. Можливі варіанти, коли діелектрична проникність в її мінімумі негативна і хиральна плазма вміщує досить широкі області непрозорості. Профілі діелектричної проникності та хвильового вектора можуть бути якісно подібними. На основе точно решаемой модели одномерного уравнения Гельмгольца рассмотрено безотражательное распространение поперечной электромагнитной волны циркулярной поляризации через хиральную неоднородную изотропную плазму с мелкомасштабными структурами высокой амплитуды. Рассмотренные пространственные профили плазмодиэлектрического хирального окружения характеризуются большим числом свободных параметров, что определяют характерные масштабы этих структур, пространственного профиля волнового вектора и поля волны, модуляции диэлектрической проницаемости и т. п. Модельные параметры соответствуют плазме без магнитного поля, но с малой добавкой хиральной компоненты (циркулярная поляризация волны обеспечена хиральностью). Выполнены численные расчеты пространственных профилей волнового вектора, амплитуды волны и диэлектрической проницаемости хиральной плазмы. Для некоторого выбора модельных параметров профиль волнового числа соответствует увеличению амплитуды волны в центре плазменного слоя. Возможны варианты, когда диэлектрическая проницаемость в ее минимуме отрицательна и хиральная плазма содержит достаточно широкие области непрозрачности. Профили диэлектрической проницаемости и волнового вектора могут быть качественно подобными.